Electrolyte Disorders Induced by Antineoplastic Drugs - Verzicco, Ignazio; Regolisti, Giuseppe; Quaini, Federico; Bocchi, Pietro; Brusasco, Irene; Ferrari, Massimiliano; Passeri, Giovanni; Cannone, Valentina; Coghi, Pietro; Fiaccadori, Enrico; Vignali, Alessandro; Volpi, Riccardo; et al. (Frontiers in Oncology, 2020)
TThe use of antineoplastic drugs has a central role in treatment of patients affected by cancer but is often associated with numerous electrolyte derangements which, in many cases, could represent life-threatening conditions. In fact, while several anti-cancer agents can interfere with kidney function leading to acute kidney injury, proteinuria and hypertension, in many cases alterations of electrolyte tubular handling and water balance occur. This review summarizes the mechanisms underlying the disturbances of sodium, potassium, magnesium, calcium and phosphate metabolism during anti-cancer treatment. Platinum compounds are associated with sodium, potassium and magnesium derangements while alkylating agents and Vinca alkaloids with hyponatremia due to syndrome of inappropriate antidiuretic hormone secretion (SIADH). Novel anti-neoplastic agents, such as targeted therapies (monoclonal antibodies, tyrosine kinase inhibitors, immunomodulators, mammalian target of rapamycin), can induce SIADH-related hyponatremia and, less frequently, urinary sodium loss. The blockade of epidermal growth factor receptor (EGFR) by anti-EGFR antibodies can result in clinically significant magnesium and potassium losses. Finally, the tumor lysis syndrome is associated with hyperphosphatemia, hypocalcemia and hyperkalemia, all of which represent serious complications of chemotherapy. Thus, clinicians should be aware of these side effects of antineoplastic drugs, in order to set out preventive measures and start appropriate treatments.